Analisis pertumbuhan, efektivitas dan kontribusi penerimaan BUMD terhadap pendapatan asli daerah Kabupaten Bandung - Dewi, Laura Evita (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Regional Owned Enterprises (BUMD) as a source of Regional Original Income (PAD) for Regional/Provincial/Regency/City Governments which are obtained from the distribution of profits/dividends from capital participation made by local governments to BUMDs. Proceeds from the distribution of profits/dividends from the BUMD will then be used to finance development in the area of the Regional Government. This research was conducted in Bandung Regency with the aim of looking at the growth, effectiveness and contribution given by BUMD to increasing PAD in Bandung Regency in the period 2016 to 2020. The data used is secondary data carried out with technical documentation. CaLK obtained from the Bandung Regency BPKAD. The analysis uses a quantitative approach by using secondary data sources consisting of the budget and the realization of PAD originating from BUMD and PAD Bandung Regency. The results show that in the last five years the growth of BUMD revenue has fluctuated an average of 7.94%, the effectiveness level of BUMD revenue is on average 102.89% or very effective, however, the contribution of BUMD revenue to PAD is on average 0 , 63% or very less.